Multicenter population‐based study on the prevalence of early onset dementia in Japan: Vascular dementia as its prominent cause. Issue 3 (29th December 2013) - Ikejima, Chiaki; Ikeda, Manabu; Hashimoto, Mamoru; Ogawa, Yusuke; Tanimukai, Satoshi; Kashibayashi, Tetsuo; Miyanaga, Kazuo; Yonemura, Kimie; Kakuma, Tatsuyuki; Murotani, Kenta; Asada, Takashi
<x xml:space="preserve">Abstract</x> Aim In Japan, the government and media have become aware of the issues of early onset dementia (EOD), but policies for EOD have not yet been established and support systems are inadequate. To provide practical data about EOD, a two‐step postal survey was performed. Methods A questionnaire requesting information on EOD cases was sent to target institutions in five catchment areas in Japan. According to the answers from the institutions, we estimated the prevalence of EOD using census data and determined the illnesses causing EOD. As a quality control study, the authors reviewed every diagnosis in a quarter of the reported cases using the medical and psychiatric records and neuroimaging data. This study was conducted from 2006 to 2007. Results Information from 2469 patients was collected from 12 747 institutions, and 2059 subjects with EOD were identified. The estimated prevalence of EOD was 47.6 per 100 000 (95% confidence interval, 47.1–48.1) for all of Japan. Of the illnesses causing EOD, vascular dementia (VaD) was the most frequent (39.8%), followed by Alzheimer's disease. Conclusions The prevalence of EOD in Japan appeared to be similar to that in Western countries. However, unlike previously reported international experience, VaD was the most frequent cause of EOD in all catchment areas in Japan.